Temporal nutrient dynamics in the Mediterranean Sea in response to anthropogenic inputs - Ji‐Young Moon; Kitack Lee; Toste Tanhua; Nurit Kress; Il‐Nam Kim (Geophysical Research Letters)
Abstract The temporal dynamics of the concentrations of nitrate (N), phosphate (P), and the N:P ratio in the upper water column (200–600 m) of the Mediterranean (MED) Sea were investigated using observational data (~123,100 data points) collected between 1985 and 2014. The studied variables were found to evolve similarly in the western and eastern MED Sea. In both basins, the N concentration increased during the first part of the observational period (1985–1998), and the temporal trend of N was broadly consistent with the history of riverine and atmospheric nitrogen input from populated areas in Europe, with a lag period of 20 years. In subsequent years, the N concentration was high and relatively constant between 1998 and 2005, after which N decreased gradually, although the decreasing trend was indistinct in the western basin. In particular, the trend of constant then declining N after 1998 is consistent with the history of pollutant nitrogen emissions from the European continent, allowing a 20 year lag following the introduction of regulation of pollutant nitrogen in the 1970s. The three‐phase temporal transition in P in both basins was more consistent with the riverine phosphorus input, with a lag period of 20 years. Our analysis indicates that the recent dynamics of N and P in the upper MED Sea has been sensitive to the dynamics of anthropogenic nitrogen and phosphorus input from atmospheric deposition and rivers.